A case report of relapsed and refractory multiple myeloma with multifocal extramedullary infiltration and pulmonary adenocarcinoma - DU Fang; ZHOU Lingyun; CHEN Jiao; LIU Danbo; XIANG Hongxian; CHEN Haifei (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Multiple myeloma (MM) remains an incurable disease, with most patients experiencing multiple relapses before ultimately progressing to refractory stage. Extramedullary infiltration is a common manifestation of relapse. However, distinguishing synchronous multifocal extramedullary infiltration from secondary malignancies poses significant diagnostic challenges. This study presents a case of relapsed refractory MM with multifocal extramedullary infiltration, diagnosed as coexistence of multiple myeloma extramedullary infiltration and pulmonary adenocarcinoma through multidisciplinary team (MDT) collaboration. Such coexistence is exceedingly rare in clinical practice and introduces substantial complexity in diagnosis and treatment planning. Through a comprehensive case report and literature review, this paper explores the diagnostic and therapeutic approaches to managing multifocal extramedullary infiltration coexisting with secondary malignancies in MM, highlighting the pivotal role of MDT in achieving precise diagnosis and optimizing patient outcomes.